PENGARUH EKONOMI SYARIAH DALAM PENGEMBANGAN INDUSTRI HALAL DI INDONESIA - Natsir, Imron (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
The halal industry in Indonesia has witnessed substantial growth, propelled by the escalating demand for halal products and services both domestically and internationally. This research delves into the pivotal role of Islamic economics in nurturing the advancement of the halal industry in Indonesia. Employing a qualitative methodology, the study scrutinizes the fundamental tenets of Islamic economics, such as equity, transparency, and prohibition of interest, and their application within the halal domain. The results indicate that the incorporation of Islamic economic principles plays a vital role in fostering the expansion of the halal industry by ensuring adherence to Sharia standards, bolstering consumer confidence, and facilitating entry into broader markets. Moreover, the study underscores challenges pertaining to regulatory frameworks, certification procedures, and public awareness. Recommendations are proffered to enhance the alignment between Islamic economic practices and the halal industry, with the aim of bolstering the competitiveness of Indonesia's halal sector